The comparative study between Islamic pawnshop (Ar Rahn) and the conventional pawnshop in Kelantan regarding their system, concept of operation and the acceptance among muslim customers / Zainudin Awang and Mohamad Safri Ya - Awang, Zainudin; Ya, Mohamad Safri (2004)
The pawnshops, popularly known as "small man's bank", have grown as the main informal financial institutions in Malaysia. They are popular among the less-educated low-income earners who are not eligible to obtain loans from formal financial institutions. There are two types of pawnshop systems - conventional and Islamic. The conventional system operates under the Pawnbrokers Act 1972. Under the act, the pawn broker is allowed to impose a monthly interest rate of up to 2%, which is very high considering the loan is secured by collaterals, which is three to four times higher. Furthermore, the pawnbroker can increase the interest rate for any loan extension or the collaterals being forfeited if the pawn is not redeemed within the stipulated time. All in all the conventional pawnbrokers are considered as "blood-suckers" who are taking advantage on the poor. In 1990, the Islamic pawnbrokers emerged as an alternative for the Muslim customers. The Islamic pawnbroking system operates under pawnbroker act 1972 (amended). The transaction is carried out according to Al-QardhulHassan and Wadiah Yad-Dhamammah principle which is free of riba'. The customer only pay a safe keeping fee, which is much lower than the interest charged by the conventional pawnbrokers. Furthermore, the collaterals will not be forfeited or auctioned without the consent from the owner. This system should be seen and considered as an attractive alternative by the customers, especially the Muslims. But the response by the Muslims is very discouraging. The researcher found the poor response to be due to low awareness on Islamic principles, unwillingness to switch to a new system with new rules and regulations, poor exposure on benefits offered by Islamic system and ineffective promotional tools in reaching the Muslim customers. Altogether, there were 24 factors being studied under both systems and some of these factors are found to be significantly different between the Islamic and conventional pawnbrokers.